Teams or tournaments? A field experiment on cooperation and competition among university students - Maria Bigoni; Margherita Fort; Mattia Nardotto; Tommaso Reggiani (Institute for the Study of Labor (IZA), 2011)
This paper assesses the effect of two stylized and antithetic non-monetary incentive schemes on students' effort. We collect data from a field experiment where incentives are exogenously imposed, performance is monitored and individual characteristics are observed. Students are randomly assigned to a tournament scheme that fosters competition between coupled students, a cooperative scheme that promotes information sharing and collaboration between students and a control treatment in which students can neither compete, nor cooperate. In line with theoretical predictions, we find that competition induces higher effort with respect to cooperation and cooperation does not increase effort with respect to the baseline. However, this is true only for men, while women do not seem to react to non-monetary incentives.
urn:nbn:de:101:1-201107283696
Keywords: A22; C93; I20; 330; education; field experiments; incentives; competition; cooperation